Selection and use of the teaching books of sciences by teachers of the fundamental teaching of the municipality Caridade of Piauí, Brazil-Seleção e uso dos livros didáticos de ciências por professores do ensino fundamental do município Caridade do Piauí, Brasil - Wellington da Silva Santos; Michelli Ferreira dos Santos; Marcones Ferreira Costa (Universidade Estadual de Alagoas, 2020)
n Brazil the textbook was regulated with the legislation created in 1938 by the decree of law 1006. The textbooks were increasingly used and to ensure distribution in public schools the federal government created the National Textbook Program (PNLD) through Decree No. 91.542 / 85. This research aimed to analyze the process of choosing and using the science textbook by elementary school teachers in the municipality of Caridade do Piauí. Twenty science teachers from the largest public elementary schools in the municipality were interviewed. Through this research it was observed that teachers do not strictly follow the PNLD guidelines for choosing books, most also revealed that they did not use or had access to the Textbook Guide to select books. Most teachers reveal that they choose teaching material based on criteria they set themselves. Although they do not follow PNLD's instructions for choosing, current science books worked in schools have been well evaluated by teachers on various criteria such as theoretical content, visual aids, proposed activities and additional resources. Regarding the interference of the internet in the use of textbooks, most teachers state that books remain the main material used in the classroom. From all these aspects we can conclude that most teachers do not follow the guidelines of PNLD and Textbook Guide to make textbook choices.